Government Size and Macroeconomic Volatility. (24th January 2017) - Collard, Fabrice; Dellas, Harris; Tavlas, George
Abstract : We examine the implications of government size for macroeconomic volatility in a standard New‐Keynesian model with multiple shocks. Larger government size mitigates volatility arising from technology, preference, mark‐up and monetary policy shocks, but amplifies that emanating from expenditure shocks. The degree of mitigation‐amplification varies with the size of government, which opens up the possibility of a non‐monotone relationship between volatility and government size. When we estimate the model on US data we find that the relationship is negative around the current US size, but it could eventually turn positive as the ratio of government spending to GDP increased. The location of the turning point in this relationship depends mainly on the type of private expenditure crowded out by higher government spending and on the degree of price stickiness.